2012
DOI: 10.1177/0192513x12468099
|View full text |Cite
|
Sign up to set email alerts
|

Outsourcing of Domestic Tasks

Abstract: The outsourcing of domestic tasks is an important strategy for coping with the competing time claims of the family and the workplace. Previous research explained the use of domestic help mainly in terms of financial and time constraints. In this article, we conceptualize household work as producing not only goods but also direct utility, and we argue that the more pleasure household members take in doing domestic work, the less they outsource it. Using the Dutch Time Competition Survey (N = 736), we find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Regular paid in-home childcare is rare in Australia, but formal nonparental childcare is associated with reductions of maternal supervisory childcare time (Bittman et al 2004;Craig and Powell 2013). Our findings are consistent with the findings of Van der Lippe et al (2004) who found that, in Dutch households, domestic outsourcing reduces women's cleaning time.…”
Section: /Does Paid Help Reduce Men's and Women's Subjective Time Prsupporting
confidence: 88%
See 4 more Smart Citations
“…Regular paid in-home childcare is rare in Australia, but formal nonparental childcare is associated with reductions of maternal supervisory childcare time (Bittman et al 2004;Craig and Powell 2013). Our findings are consistent with the findings of Van der Lippe et al (2004) who found that, in Dutch households, domestic outsourcing reduces women's cleaning time.…”
Section: /Does Paid Help Reduce Men's and Women's Subjective Time Prsupporting
confidence: 88%
“…Since most men do little indoor domestic work, outsourcing these tasks may not affect their time allocation, as found by Van der Lippe et al (2004). But if outsourcing is directed at tasks more typically done by men, we may observe negative associations with their domestic time.…”
Section: Does Paid Help Reduce Men's and Women's Time On And Share Ofmentioning
confidence: 70%
See 3 more Smart Citations